DETEKSI E. coli PENGHASIL Extended Spectrum Beta-Lactamase (ESBL) MENGGUNAKAN METODE PCR PADA SAMPEL AIR BERSIH - Lella Rahmawati; Retno Sasongkowati; Anita Anggraini; Deddy Adam (Poltekkes Kemenkes Surabaya, 2022)
Escherichia coli is a normal flora in the human body that plays an important role in the digestive process. The presence of Escherichia coli ESBL (Extended Spectrum Beta-Lactamase) bacteria in clean water samples indicates environmental pollution originating from feces. The aquatic environment is the most influential ecosystem in human life. These contaminated ecosystems provide optimal conditions for antibiotic-resistant bacteria from various sources to mix and transfer their resistance genes to clinically important bacteria for the development of human pathogens with novel resistance mechanisms. This study aims to determine the percentage of ESBL-producing E. coli bacteria in clean water samples. This study uses a descriptive observational design. The total sampling is 195 clean water samples. After going through screening in the form of membrane filter tests, KIA, and IMVIC, 25 isolates were found which were declared as E. coli. Analysis of the ESBL-producing E. coli gene using conventional PCR. Analysis of the Molecular Weight value in the sample using the GelAnalyzer 19.1 application. Based on these calculations, it was found that samples of E. coli isolates containing the ESBL gene were 24% of the 25 E. coli isolates. This percentage indicates that there is a large enough contamination in clean water. The results of this study indicate a potential risk to public health. The participation of health workers, government and the community in maintaining sanitary hygiene is needed to avoid greater contamination of antibiotic-resistant bacteria.